A hybrid particle swarm optimization and bacterial foraging for power system stability enhancement. Issue 2 (11th September 2014) - Abd‐Elazim, S. M.; Ali, E. S.
Abstract : A novel hybrid approach involving particle swarm optimization (PSO) and bacterial foraging optimization algorithm (BFOA) called bacterial swarm optimization (BSO) is illustrated for designing static var compensator (SVC) in a multimachine power system. In BSO, the search directions of tumble behavior for each bacterium are oriented by the individual's best location and the global best location of PSO. The proposed hybrid algorithm has been extensively compared with the original BFOA algorithm and the PSO algorithm. Simulation results have shown the validity of the proposed BSO in tuning SVC compared with BFOA and PSO. Moreover, the results are presented to demonstrate the effectiveness of the proposed controller to improve the power system stability over a wide range of loading conditions. © 2014 Wiley Periodicals, Inc. Complexity 21: 245–255, 2015